The untamed warrior's bride - Willingham, Michelle (Author of historical romances) (Harlequin historicals., 2023)
"Piers of Grevershire might have been born illegitimate, but he'll fight for the land he knows is his. To do so, he must win Lady Gwendoline's hand in marriage! What starts as a secret mission of vengeance soon becomes more as Gwen's unique fire ignites a powerful connection between them. And when they're married, Piers finds earning Gwen's trust means revealing his true identity--and the betrayal that risks destroying their fledgling bond..."--